(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Complaining of tearing was found in some of the patients after cataract surgery (both Phacoemulsification and Small Incision Cataract Surgery) for age related cataract, among male and female patients with an increased incidence among female and more elderly patients. Secondary acquired lacrimal drainage obstruction has been proposed to develop due to different causes like infections and inflammation of the lacrimal drainage system. Watering eyes are observed after cataract surgery may be due to surgical trauma, inflammation of the anterior segment of the operated eye, frequent use of topical medications during the post operative periods and less forceful blinking by the patients in early postoperative days. Objective: To determine the effects of cataract surgery (both Phacoemulsification and Small Incision Cataract Surgery) on lacrimal drainage system in eyes with age related cataract. Methods: This cross-sectional study was performed on 100 eyes of 100 patients with age related cataract. Among the patients, 64 were male and 36 were female. All the patients were Armed Forces personnels (both serving, retired and civilians) and their parents. The average age of the patients were 61.6±8.92 years ranging from 51 to 80 years. According to age, the patients were divided in three age-group (51-60 years; 61-70 years; 71-80 years). The patients were equally divided in two groups. In group-I(n=50), patients were done Phacoemulsification and posterior chamber intraocular lens (PCIOL) implantation and in group-II(n=50), patients were done Small Incision Cataract Surgery (SICS) and PCIOL implantation in one eye. All the patients were operated under peribulbar anesthesia. Included patients had Fluorescein Disappearance Test (FDT) and Taste test duration of ?5.7 minutes in both eyes before operation. Tear drainage function tests were repeated for one week and one month after surgery in both eyes and obtained data were compared. Results: The incidence of watering eyes after phacoemulsification surgery in eyes treated for age related cataract was 17% at the end of first week and 09% after one month. The mean taste test duration time was 3.83±0.76 minutes before surgery, 5.33±2.45 minutes after a week and 4.27±1.53 minutes one month after surgery. After SICS the incidence of lacrimal drainage impairment was 19% at the end of first week and 12% after one month. The mean Taste test duration time was 3.83±0.76 minutes before surgery, 5.62±2.84 minutes after a week and 4.36±1.85 minutes one month after surgery. However, more number of elderly patients developed watering eyes than the lower age group. Among the patients, from 71-80 years age group, 05 patients (19.23%) developed watering eyes. There was slight difference between male and female in complaining of tearing after operation. Out of 64 male, 11 patients (approximately 17.18%) were observed watering eyes in first week follow up. Among 36 female, 07 patients (approximately 19.44%) complained of watering in first week follow up. No difference of watering was observed in respect of socio-economic conditions. No post operation complains of watering eyes was observed in the sound eyes (non-operated) of the patients. Conclusion: Watering eyes may develop cataract surgery (both Phacoemulsification and SICS) in eyes with age related cataract, among male and female patients with an increased incidence among female and more elderly patients. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014